Comparison of air-displacement plethysmography results using predicted and measured lung volumes over a protracted period of time - Otterstetter, Ronald; Johnson, Kelly E.; Kiger, Dana L.; Agnor, Sarah E.; Kappler, Rachele M.; Reinking, Megan; Tessmer, Kathryn (Clinical physiology and functional imaging, 2015)
Summary Background Air‐displacement plethysmography (ADP) systems can either measure or predict lung volume (LV) in their test trials. The repeatability of the predicted and the measured value is an important factor in the accuracy of the final test result. Objective Compare the variability and accuracy of ADP tests using predicted and measured LV over a protracted period of time. Methods Twenty‐four adults (18–30 years) participated in the study. Each subject underwent three ADP tests over a period of 3 weeks, with 1 week between tests. At each testing session, subjects were tested using a predicted LV protocol and a measured LV protocol in random order. LV, body volume (BV) and per cent body fat (% BF) were compared between testing modes and between assessment times. Results A two‐way ANOVA examined the effect of the mode of LV assessment (measured or predicted) and trial (week) for LV and BV and the effect of the LV mode assessment (measured or predicted) and trial (week) on % BF results. LV and BV did not differ significantly (P>0·05) between the two modes of assessment (measured or predicted). Time (day of assessment) also was not significantly different between trials (P>0·05). Neither mode nor trial was significant (P>0·05), therefore neither had an effect on the % BF results. Conclusion In this investigation, the method used to determine LV during ADP testing did not significantly affect the final % BF result. Also, tests performed over an extended period of time was not affected by LV measurement method.